Modification of Oudin's method of single immunodiffusion in agar gel for detection of IgA in bronchoalveolar lavage of white mice - Libich, J; Franĕk, J; Tucková, L (Folia microbiologica, 1983)
Oudin's principle of single immunodiffusion in agar gel was modified for quantitative determination of IgA in bronchoalveolar lavage (BAL) of normal 20-25 g mice. The reaction took place at 25 degrees C in 0.3% agarose with 16.7% pig serum against mouse IgA, and was evaluated on the basis of a relationship between the progress of the precipitin zone and the square root of time. The linear dependence of the derived constant k on the logarithmic concentration of antibody in the sample permitted to express the results as titre, corresponding to a dilution where k = 0. Examination of seven samples of pooled blood serum of normal mice showed that (1) the IgA level was practically constant, (2) serum IgA possessed under given conditions similar properties as IgA from the bronchoalveolar secretion; it is therefore possible to employ pooled sera as a reliable control of the immunodiffusion system in case of lack of reference standards with defined IgA content. Examination of 82 individual BAL samples of normal mice revealed that the mean IgA concentration in 2.5 mL samples was almost 1000 times lower than in blood serum.
Keywords: Bronchi; imunoglobulin A sekreční; referenční hodnoty; Immunodiffusion; imunodifuze; Mice; Pulmonary Alveoli; Reference Values; Immunoglobulin A, Secretory; Therapeutic Irrigation; Animals; mužské pohlaví; Male; zvířata; myši; léčebná irigace; bronchy; plicní alveoly